2022
DOI: 10.1001/jamaophthalmol.2022.3627
|View full text |Cite
|
Sign up to set email alerts
|

Association of Race, Ethnicity, and Socioeconomic Status With Visual Impairment in Adolescent Children in the US

Abstract: ImportanceAlthough racial, ethnic, and socioeconomic disparities in visual impairment have been described in adults, few studies have focused on the adolescent population, which may provide insight into the emergence of vision health inequities.ObjectiveTo describe visual health disparities among adolescent children in the US.Design, Setting, and ParticipantsThis was a cross-sectional study of adolescents from the 2005 to 2008 National Health and Nutrition Examination Survey. Participants were aged 12 to 18 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…Su et al found that lower educational attainment, food insecurity, and having Medicaid were associated with self-reported visual difficulty. Ko et al found that poverty and having less than a high school education were associated with BCVA among adults and Adomfeh et al found that race, ethnicity, and not being a US citizen were associated with presenting vision impairment among adolescents. Lower incomes and lower levels of education have also been associated with increased odds of diabetic retinopathy …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Su et al found that lower educational attainment, food insecurity, and having Medicaid were associated with self-reported visual difficulty. Ko et al found that poverty and having less than a high school education were associated with BCVA among adults and Adomfeh et al found that race, ethnicity, and not being a US citizen were associated with presenting vision impairment among adolescents. Lower incomes and lower levels of education have also been associated with increased odds of diabetic retinopathy …”
Section: Discussionmentioning
confidence: 99%
“…Studies investigating how social determinants of health (SDOH) affect vision loss suggest that race and ethnicity, income, educational attainment, and food security are associated with vision outcomes . However, with a few exceptions, these studies rely on self-reported data.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in the 2005 to 2008 National Health and Nutrition Examination Survey cohort, the most recent cohort to include both visionrelated questionnaires and eye examinations of adolescents, 12-to 18-year-olds who identified as Black, Mexican American, lowincome, and non-U.S. citizens were more likely to have worse subjective and objective visual functioning. 29 Because youth value their eyesight highly, eye care programs that improve access for marginalized youth, such as high school-based eye clinics, may help to address these external barriers. 30 School-based vision programs may also improve students' academic performance.…”
Section: Discussionmentioning
confidence: 99%
“…Although youth in this study identified appearance, cost, inconvenience, and discomfort as key barriers to eyeglasses, epidemiologic studies have found additional socioeconomic barriers to eye care. For example, in the 2005 to 2008 National Health and Nutrition Examination Survey cohort, the most recent cohort to include both vision-related questionnaires and eye examinations of adolescents, 12- to 18-year-olds who identified as Black, Mexican American, low-income, and non-U.S. citizens were more likely to have worse subjective and objective visual functioning 29 . Because youth value their eyesight highly, eye care programs that improve access for marginalized youth, such as high school–based eye clinics, may help to address these external barriers 30 .…”
Section: Discussionmentioning
confidence: 99%